Pendekatan kontekstual dalam pengajaran dan pemelajaran bahasa (Jurnal Bahasa, 2003)
The contextual approach in the teaching and learning of language calls for the association of teaching materials in the real situations. The objective is to motivate the students in relating their knowledge in the actual situations. It can be achieved by orientating the contextual learning and teaching into seven major elements: constructism, questions, inquiry, educational community, modelling, reflextions, and authentic assessments